Analisis Kritik Murtadha Muthahhari Terhadap Konsep Etika Barat - Rany Mulyani (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
This article contains a comprehensive analysis of Murtadha Mutahhari's critique of the Concept of Western Ethics. Some of the themes discussed in this article are examining the philosophical foundations of Murthada Mutahhari, Murthada Mutahhari's criticism of moral concepts, human rights, and Murthada's criticism of the concept of man in western ethics. To explore these important issues, this research uses library research and character studies. The findings in this study show that sexual ethics in Murtadha Mutahhari's view, that every act that leads humans to perfection is goodness. Second, that the concept of morality criticized by Murtadha Mutahhari is the theory of emotion which states that morality is love, and the theory of intuition which states that moral actions are the result of intuition commands.